Ferroptosis and Alzheimer’s disease: unraveling the molecular mechanisms and therapeutic opportunities - Fang, Yuan; Han, Zhongyu; Yang, Siming; Chen, Juncheng; Li, Ruobing; Zhang, Zhexu; Song, Junhui; Wang, Danyan; Ban, Yunqing (Frontiers in Cell and Developmental Biology, 2026)
Ferroptosis is a novel form of regulated cell death. Compared with other types of cell death, it shows great differences in structure and biochemistry. This type of cell death is receiving increasing attention. For example, studies have found that it plays a key role in the development of neurodegenerative diseases underlying brain atrophy, such as Alzheimer’s disease (AD). AD is a chronic and worsening neurodegenerative disease. It poses a serious threat to the health and quality of life of the elderly. The pathology of AD is mainly the presence of extracellular beta-amyloid (Aβ) plaques and intracellular tau-based nerve fiber entanglement (NFTs). Although there are a large number of studies and interventions for AD, so far, no clinical drugs have been found that can stop the pathological progression of AD or cure it. Currently, treatment strategies for this disease only focus on alleviating clinical symptoms and do not achieve slowing disease progression or curing it. Ferroptosis is gradually considered to play a key role in the occurrence and development of AD. Research based on the AD model confirms that neuronal ferroptosis can be inhibited through pharmacology to reverse cognitive disorders. In this review, we first describe the key molecular mechanisms of ferroptosis, and then discuss how these mechanisms operate and develop in AD. Then, we give a detailed introduction to the latest treatments for AD, including iron chelators, antioxidants, and specific ferroptosis inhibitors. What is noteworthy is that this article emphasizes the analysis of the mechanisms of iron metabolism disorders, as well as the introduction of new drugs for the prevention, rather than the alleviation of AD.